Expanded Disability Status Scale (EDSS) in Multiple Sclerosis - Serkan Demir (Cam & Sakura Medical Journal, 2022)
Multiple sclerosis has an increasing prevalence and incidence. There are many articles showing that early treatment can prevent possible disability. Expanded disability status scale assessmenthas great importance both in pivotal studies and in clinical practice to evaluate treatment efficacy. For this reason, this review has been written to be well known and not to miss the details.